2016
DOI: 10.1109/tasc.2016.2542270
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Pinning Landscapes for Enhanced 2G Coil Wire

Abstract: We demonstrate a 2-fold increase of the in-field critical current of AMSC's standard 2G coil wire by irradiation with 18 MeV Au ions. The optimum pinning enhancement is achieved with a dose of 6x10 11 Au ions/cm 2 . Although the 77 K, self-field critical current is reduced by about 35%, the in-field critical current (H//c) shows a significant enhancement between 4 -50K in fields >1 T. The process was used for the roll-to-roll irradiation of AMSC's standard 46 mm wide production coated conductor strips which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 17 publications
(30 reference statements)
1
40
0
1
Order By: Relevance
“…3). 2D modeling predicts faster demagnetization rate by33,35, and 39 % for 50, 100, and 150 mT ripple field amplitudes, respectively, as calculated for the 20th cycle.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…3). 2D modeling predicts faster demagnetization rate by33,35, and 39 % for 50, 100, and 150 mT ripple field amplitudes, respectively, as calculated for the 20th cycle.…”
mentioning
confidence: 78%
“…Their Hastelloy substrate enhances mechanical properties. Also, the stack lenght is virtually unlimited with very uniform J c , and the stack width could be as wide as 46 mm [3]. Larger continuous superconducting shapes result in larger trapped flux for the same maximum trapped field.…”
Section: Introductionmentioning
confidence: 99%
“…These defects produced by ion irradiation would account for the depression of T c in YBa 2 Cu 3 O y (YBCO), which is proportional to the average number of defects23. Recently, a low-energy ion irradiation has been revisited and suggested as a practically feasible approach to improve flux pinning in YBCO242526. In single crystals of iron-based superconductors, it has been found that ion irradiations, as a whole, improve J c and its J c enhancements persist up to much higher fluencies than in cuprate superconductors, although T c is suppressed with increasing irradiation doses272829.…”
mentioning
confidence: 99%
“…The initial increase of S(T) corresponds to an Anderson-Kim like creep with S≈T/U, where U is the activation energy (approximately Tindependent at low T). The IRR0 displays a peak at T≈20 K, usually attributed to correlated disorder (such as twin boundaries) [9], but which also can be attributed to changes in the strong pinning regimes for nanoparticles [18]. Above the peak, the S(T) relaxation displays a minimum which is usually attributed to glassy relaxation with values determined by the vortex bundle size.…”
Section: Resultsmentioning
confidence: 99%